High-strength high-toughness oxygen-enriched ablation resistant nickel-based superalloy and additive manufacturing method thereof

By optimizing the alloy composition and manufacturing process, the problem of oxygen-rich ablation resistance of high-temperature alloys in the liquid rocket engine environment was solved, and the high-temperature strength and ductility of the alloys were improved, meeting the manufacturing requirements of complex structural components.

CN121674783APending Publication Date: 2026-03-17RESEARCH INSTITUTE OF ADVANCED MATERIALS (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511898829.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing high-temperature alloys lack sufficient resistance to oxygen-enriched ablation in the high-temperature, high-pressure, high-load, and oxygen-enriched gas environments of liquid rocket engines, and are prone to thermal cracking and other defects during additive manufacturing, which limits their application.

Method used

A high-strength, high-toughness, and oxygen-enriched ablation-resistant nickel-based superalloy was designed. By strictly controlling the content of elements such as Co, Cr, W, Mo, Al, Ti, Nb, C, B, and Zr, and combining additive manufacturing process parameters such as solution treatment and aging treatment, the high-temperature strength and oxygen-enriched ablation resistance of the alloy were ensured.

Benefits of technology

It achieves tensile strength ≥1000MPa, yield strength ≥900MPa, and elongation ≥8% at 650℃, and a combustion length ≤20mm in an oxygen-rich environment at room temperature, meeting the structural and performance requirements of hot-end components of liquid rocket engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121674783A_ABST
    Figure CN121674783A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of superalloys and preparation, and particularly relates to a high-strength high-toughness oxygen-enriched ablation resistant nickel-based superalloy and an additive processing method thereof. The nickel-based high-temperature alloy is mainly prepared from the following raw materials in percentage by mass: 12%-18% of Co, 14%-18% of Cr, 0%-4% of W, 0%-1% of Mo, 0.5%-2.0% of Al, 1.5%-3.5% of Ti, 0%-1.0% of Nb, 0%-0.5% of Fe, 0%-0.5% of Mn, 0%-0.5% of Si, 0.01%-0.08% of C, 0.001%-0.01% of B, 0.01%-0.05% of Zr and the balance of Ni and inevitable impurities. According to the nickel-based high-temperature alloy powder and the preparation method thereof, by strictly regulating and controlling the types and the using amount of the alloy components, the nickel-based high-temperature alloy powder is good in compatibility with the additive manufacturing process, the hot tearing phenomenon in the additive manufacturing process is effectively restrained, and the high-temperature alloy has excellent high-temperature strength and high-temperature ductility after being subjected to heat treatment; and the high-temperature alloy has excellent oxygen-enriched ablation resistance, and can be used for preparing complex structural parts.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of high-temperature alloys and preparation, and particularly relates to a high-strength and high-toughness oxygen-rich ablation-resistant nickel-based high-temperature alloy and an additive manufacturing method thereof. BACKGROUND

[0002] The nickel-based high-temperature alloy is widely used in the hot end components of advanced aeronautical and aerospace engines due to its excellent high-temperature mechanical properties, and the development and manufacturing of the nickel-based high-temperature alloy is one of important symbols for measuring the material development level of a country.

[0003] The liquid rocket engine adopts an oxygen-rich, high-pressure and over-and-under cycle mode, and the working environment is an oxygen-rich gas with high temperature, high pressure, high load and large flow. In such a harsh service environment, the metal material is prone to combustion, accompanied by a sharp rise in temperature and a violent release of heat, which can easily lead to fire and even explosion and other dangerous accidents.

[0004] In such a harsh service environment, in addition to the requirement of excellent high-temperature mechanical properties of the material, the oxygen-rich ablation resistance of the material is also extremely high. At present, the hot end components of the liquid rocket engine often use high-temperature alloys (such as GH4169), but the oxygen-rich ablation resistance of these high-temperature alloys has been unable to meet the development needs of advanced liquid rocket engines.

[0005] Additive manufacturing has attracted widespread attention due to its high degree of freedom in design and manufacturing, short manufacturing cycle and no need for tooling molds. However, during the additive manufacturing process, the alloy melt often experiences fast heating, fast cooling and strong constraint, resulting in a large temperature gradient in the final additive manufacturing component, which easily induces thermal cracks and other defects, thereby restricting the application of advanced high-temperature alloys.

[0006] In view of this, the present application is proposed. SUMMARY

[0007] Based on the above technical background, the main purpose of the present application is to provide a high-strength and high-toughness oxygen-rich ablation-resistant nickel-based high-temperature alloy and an additive manufacturing method thereof to overcome the deficiencies in the prior art.

[0008] To achieve the foregoing purposes, the technical solutions adopted by the present application include: The first aspect of the present application is to provide a high-strength and high-toughness oxygen-rich ablation-resistant nickel-based high-temperature alloy, which is prepared from raw materials including the following mass percentages: Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance of Ni and inevitable impurities.

[0009] Preferably, the high-strength and high-ductility oxygen-rich ablation-resistant nickel-based high-temperature alloy material is prepared from raw materials comprising the following mass percentages: Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance of Ni and inevitable impurities.

[0010] More preferably, in the nickel-based high-temperature alloy material, the content of each element can be as follows, respectively, in mass percentage: The mass percentage of Co element can be 12%, 13.5%, 14.2%, 15.6%, 16.1%, 17.4%, 18%, or a range formed by any two of them. Co element has low combustion heat, only 4.06 kJ / g, and the addition of Co element can effectively inhibit the oxygen-rich combustion behavior of the alloy. On the other hand, Co element can reduce the stacking fault energy of the alloy system, stimulate the stacking fault or twinning deformation mechanism, and improve the high-temperature elongation of the alloy. However, when the content of Co is too high, brittle B2-type phases are easily formed, and the cost of the alloy is also increased. In the present application, the content of Co is controlled in the range of 12% to 18%, which can improve the high-temperature strength and toughness and the oxygen-rich ablation resistance of the alloy while controlling the cost of the alloy.

[0011] The mass percentage of Cr element can be 14%, 15.3%, 16%, 17.6%, 18%, or a range formed by any two of them; Cr element itself is a strong carbide-forming element, and an appropriate amount of Cr element can promote the alloy to form Cr 23 C6-type carbide to strengthen the grain boundary. However, Cr is a combustible element, with a combustion heat of 10.88 kJ / g, and excessive Cr element can significantly reduce the oxygen-rich ablation resistance of the alloy. By adjusting the content of Cr element in the range of 14% to 18%, the alloy can strengthen the grain boundary, improve the high-temperature strength and high-temperature elongation of the alloy, and also take into account the oxygen-rich ablation resistance of the alloy.

[0012] The mass percentage of W can be 0%, 0.8%, 1.2%, 2.5%, 3.3%, 4%, or any combination thereof; the content of Mo can be 0%, 0.2%, 0.5%, 0.7%, 1%, or any combination thereof. W and Mo are important solid solution strengthening elements in high-temperature alloys. In this invention, the combined use of W and Mo ensures the solid solution strengthening effect. On the other hand, the heat of combustion of W is 4.62 kJ / g, and that of Mo is 7.94 kJ / g. By designing a high-W, low-Mo composition, the alloy can be ensured to have a low heat of combustion and resistance to oxygen-rich ablation.

[0013] The mass percentage of Al can be 0.5%, 0.8%, 1.2%, 1.7%, 2%, or any combination thereof; the content of Ti can be 1.5%, 2.0%, 2.2%, 2.8%, 3.0%, 3.5%, or any combination thereof; and the content of Nb can be 0%, 0.4%, 0.7%, 1.0%, or any combination thereof. Al, Ti, and Nb are important precipitation strengthening elements in high-temperature alloys. In this invention, by limiting the content of Al, Ti, and Nb within specific ranges and using them in combination, a certain amount of γ' strengthening phase can be formed, thereby improving the high-temperature strength of the alloy. However, the heat of combustion of Al is 31.4 kJ / g, that of Ti is 15.7 kJ / g, and that of Nb is 10.46 kJ / g, all of which are easily combustible elements. In this invention, through a composition design with high Ti and low Al content, the heat of combustion of the alloy is effectively reduced while ensuring its high-temperature strength, thus improving the alloy's resistance to oxygen-rich ablation. In addition, using a relatively low Nb content can minimize the tendency for harmful precipitates to form in the alloy and avoid alloy brittleness.

[0014] The mass percentage of carbon (C) can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, or any combination thereof; the content of boron (B) can be 0.001%, 0.002%, 0.003%, 0.004%, 0.01%, or any combination thereof; and the content of zirconium (Zr) can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, or any combination thereof. Trace amounts of C, B, and Zr segregate at grain boundaries, effectively improving grain boundary bonding strength, thereby enhancing the high-temperature strength and elongation of the alloy. However, during the rapid solidification process of additive manufacturing, C, B, and Zr lower the alloy's liquidus temperature, promoting the formation of a liquid phase film at grain boundaries; under the internal stress of the additively manufactured component, this liquefaction film tears, forming hot cracks. This invention uses 0.01% to 0.08% C, 0.001% to 0.01% B, and 0.01% to 0.05% Zr to ensure the high-temperature strength and elongation of the alloy while ensuring the compatibility of the alloy with additive manufacturing processes, and can significantly suppress hot cracking of the alloy.

[0015] According to a preferred embodiment of the present invention, the high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy material is prepared from raw materials comprising the following mass percentages: Co: 16.7%, Cr: 16.4%, W: 2.0%, Mo: 0.3%, Al: 1.4%, Ti: 2.5%, Nb: 0.2%, Fe: 0.02%, Mn: 0.0034%, Si: 0.011%, C: 0.07%, B: 0.004%, Zr: 0.03%, balance Ni and unavoidable impurities.

[0016] Alternatively, according to a preferred embodiment of the present invention, the high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy material is prepared from raw materials comprising the following mass percentages: Co: 14.5%, Cr: 14.2%, W: 3.5%, Mo: 0.5%, Al: 1.2%, Ti: 2.6%, Nb: 0.4%, Fe: 0.02%, Mn: 0.03%, Si: 0.02%, C: 0.06%, B: 0.003%, Zr: 0.04%, balance Ni and unavoidable impurities.

[0017] Alternatively, according to a preferred embodiment of the present invention, the high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy material is prepared from raw materials comprising the following mass percentages: Co: 17.5%, Cr: 17.4%, W: 2.0%, Mo: 0.4%, Al: 1.2%, Ti: 2.6%, Nb: 0.2%, Fe: 0.02%, Mn: 0.04%, Si: 0.021%, C: 0.07%, B: 0.003%, Zr: 0.04%, balance Ni and unavoidable impurities.

[0018] A second aspect of the present invention is to provide an additive manufacturing method for the high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy described in the first aspect of the present invention, the additive manufacturing method comprising the following steps: Step 1: The weighed metal and non-metal raw materials are processed by additive manufacturing to prepare additive samples; Step 2: The additive sample is solution treated, air-cooled, aged, and then air-cooled to obtain a nickel-based high-temperature alloy.

[0019] The steps described above are described in detail below.

[0020] In step 1, the weighed metal and non-metal raw materials are processed into spherical pre-alloyed powder through smelting and powdering processes. The particle size range of the spherical pre-alloyed powder is 15-53 μm.

[0021] The conditions for the additive manufacturing process (3D printing) are as follows: under vacuum or protective atmosphere, the single layer thickness is set to 20-40 μm, the scanning spacing is 60-100 μm, the laser power is 200-300 W, the laser scanning rate is 800-1300 mm / s, and the laser spot diameter is 60-100 μm.

[0022] Preferably, the additive manufacturing process conditions are as follows: under high-purity argon protection, the single-layer thickness is set to 40 μm, the scanning spacing is 80 μm, the laser power is 240 W, the laser scanning rate is 1000 mm / s, and the laser spot diameter is 80 μm.

[0023] In additive manufacturing, the single-layer thickness can be 20 μm, 30 μm, 40 μm, or any combination thereof. The scanning spacing can be 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or any combination thereof. The laser power is 200 W, 220 W, 240 W, 260 W, 280 W, 300 W, or any combination thereof. The laser scanning rate can be 800 mm / s, 900 mm / s, 1000 mm / s, 1100 mm / s, 1200 mm / s, 1300 mm / s, or any combination thereof.

[0024] In step 2, the solution treatment conditions are: heat treatment at 940–1000°C for 1–5 hours.

[0025] Preferably, the solution treatment conditions are: heat treatment at 970°C for 1 hour.

[0026] This invention employs a lower solution treatment temperature, which allows for the inheritance of the microstructure characteristics of additively manufactured structural parts, further improving the high-temperature strength and elongation of nickel-based superalloys. If the solution treatment temperature is too high or the solution treatment time is too long, the microstructure characteristics of additive manufacturing can be easily eliminated, leading to insufficient high-temperature strength of the alloy. If the solution treatment temperature is too low or the time is too short, the alloying elements may not be sufficiently homogenized, making it difficult to ensure the uniform and sufficient precipitation of the γ' strengthening phase during subsequent aging heat treatment.

[0027] The air cooling rate is 10–200 °C / min. Preferably, the air cooling rate is 50–120 °C / min.

[0028] The aging treatment conditions are: heat preservation at 690-750℃ for 6-12 hours.

[0029] Preferably, the aging treatment is performed under the following conditions: heat treatment at 720°C for 8 hours.

[0030] The temperature and time of aging treatment have a significant impact on the final mechanical properties of the alloy. If the aging temperature is too low, on the one hand, element diffusion slows down, leading to slower precipitation kinetics of the γ' strengthening phase and an excessively low content of the strengthening phase, failing to meet high-temperature strength requirements; on the other hand, a low aging temperature easily induces the precipitation of harmful brittle phases, reducing the alloy's high-temperature elongation. If the aging temperature is too high, the driving force for γ' strengthening phase precipitation weakens, resulting in an excessively low equilibrium content, also failing to meet high-temperature strength requirements. This invention, by controlling the aging temperature and time, can suppress the formation of harmful brittle phases while ensuring sufficient precipitation of the γ' strengthening phase, thus maximizing the high-temperature mechanical properties of the alloy.

[0031] The air cooling rate is 10–200 °C / min. Preferably, the air cooling rate is 80–140 °C / min.

[0032] The beneficial effects of this invention are as follows: (1) By strictly controlling the type and amount of alloy components, the present invention makes the high-temperature alloy powder compatible with the additive manufacturing process and can suppress the hot tearing phenomenon in the additive manufacturing process; while taking into account the additive manufacturing process, the high-temperature nickel-based alloy improves the high-temperature strength and high-temperature elongation of the nickel-based alloy, and has excellent resistance to oxygen-rich ablation.

[0033] (2) The high-temperature performance of the additive manufacturing high-temperature nickel-based alloy structural parts of the present invention at 650℃ meets the following requirements: tensile strength ≥1000MPa, yield strength ≥900MPa, elongation ≥8%, and has high high-temperature mechanical strength and ductility.

[0034] The additively manufactured high-temperature alloy structural component of the present invention exhibits excellent resistance to oxygen-enriched ablation under the conditions of room temperature, 9MPa, pure oxygen, and Al ignition: burning length ≤20mm.

[0035] (3) The high-temperature nickel-based alloy described in this invention has high-temperature toughness and resistance to oxygen-rich ablation at 650°C, which enables the high-temperature nickel-based alloy to be used to prepare complex structural parts using additive manufacturing processes, thereby meeting the structural and performance requirements of hot-end components of liquid rocket engines. Attached Figure Description

[0036] Figure 1 Metallographic images of the alloy prepared in Example 1 are shown; Figure 2 The metallographic image of the alloy obtained in Example 2 is shown; Figure 3 The metallographic image of the alloy obtained in Example 3 is shown; Figure 4 The metallographic image of the alloy obtained in Example 4 is shown; Figure 5 The metallographic diagram of the alloy prepared in Comparative Example 4 is shown; Figure 6 The metallographic diagram of the alloy prepared in Comparative Example 5 is shown; Figure 7 The microstructure of the alloy prepared in Comparative Example 1 is shown. Figure 8 A transmission electron microscope (TEM) image of the alloy prepared in Example 1 is shown. Detailed Implementation

[0037] The present invention will now be described in detail, and its features and advantages will become clearer and more apparent from these descriptions.

[0038] Example The present invention is further illustrated below with specific examples. These embodiments are merely illustrative and not intended to limit the scope of the invention. All raw materials used in the embodiments of the present invention are commercially available.

[0039] Example 1 An additive manufacturing method for a high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy, the method comprising the following steps: The following metal and non-metal raw materials were weighed according to the following mass percentages: Co: 16.7%, Cr: 16.4%, W: 2.0%, Mo: 0.3%, Al: 1.4%, Ti: 2.5%, Nb: 0.2%, Fe: 0.02%, Mn: 0.0034%, Si: 0.011%, C: 0.07%, B: 0.004%, Zr: 0.03%, with the balance being Ni and unavoidable impurities. The above metal and non-metal raw materials were then processed using a melting and vacuum induction melting gas atomization process to prepare spherical pre-alloyed powder with a particle size of 15–53 μm.

[0040] The above-mentioned spherical pre-alloyed powder was used to prepare samples using selective laser melting (SLM) additive manufacturing. The additive manufacturing process (3D printing) parameters included: under high-purity argon protection, a single-layer thickness of 40 μm, a scanning spacing of 80 μm, a laser power of 240 W, a laser scanning rate of 1000 mm / s, and a laser spot diameter of 80 μm, to obtain the additive samples.

[0041] The obtained additive manufacturing samples were subjected to solution treatment under the following conditions: heat treatment at 970℃ for 1 h followed by air cooling at a rate of 80℃ / min. Subsequently, aging treatment was performed under the following conditions: heat treatment at 720℃ for 8 h followed by air cooling at a rate of approximately 100℃ / min.

[0042] Example 2 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The pre-alloyed powder was prepared according to the following mass percentages: Co: 14.5%, Cr: 14.2%, W: 3.5%, Mo: 0.5%, Al: 1.2%, Ti: 2.6%, Nb: 0.4%, Fe: 0.02%, Mn: 0.03%, Si: 0.02%, C: 0.06%, B: 0.003%, Zr: 0.04%, with the balance being Ni and unavoidable impurities. The particle size of the above pre-alloyed powder was 15–53 μm.

[0043] Example 3 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The pre-alloyed powder was prepared according to the following mass percentages: Co: 17.5%, Cr: 17.4%, W: 2.0%, Mo: 0.4%, Al: 1.2%, Ti: 2.6%, Nb: 0.2%, Fe: 0.02%, Mn: 0.04%, Si: 0.021%, C: 0.07%, B: 0.003%, Zr: 0.04%, with the balance being Ni and unavoidable impurities. The particle size of the above pre-alloyed powder was 15–53 μm.

[0044] Example 4 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The additive manufacturing process (3D printing) parameters include: under high-purity argon gas conditions, the single-layer thickness is set to 40 μm, the scanning spacing is 80 μm, the laser power is 280 W, the laser scanning rate is 1200 mm / s, and the laser spot diameter is 80 μm.

[0045] Example 5 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The conditions for solution treatment were: after holding at 1000℃ for 1 h, air cooling was performed at a rate of approximately 100℃ / min. Example 6 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The aging treatment conditions are: after holding at 720℃ for 12 hours, air cooling is performed at a rate of approximately 70℃ / min.

[0046] Comparative Example Comparative Example 1 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The pre-alloyed powder was prepared according to the following mass percentages: Co: 16.8%, Cr: 7.9%, W: 0.01%, Mo: 0.02%, Al: 1.5%, Ti: 3.4%, Nb: 0.02%, Fe: 0.02%, Mn: 0.0024%, Si: 0.021%, C: 0.05%, B: 0.003%, Zr: 0.01%, with the balance being Ni and unavoidable impurities. Comparative Example 2 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The pre-alloyed powder was prepared according to the following mass percentages: Co: 16.7%, Cr: 8.0%, W: 2.1%, Mo: 0.3%, Al: 1.6%, Ti: 3.5%, Nb: 0.02%, Fe: 0.02%, Mn: 0.0034%, Si: 0.021%, C: 0.07%, B: 0.003%, Zr: 0.02%, with the balance being Ni and unavoidable impurities. Comparative Example 3 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The pre-alloyed powder was prepared according to the following mass percentages: Co: 16.6%, Cr: 16.6%, W: 2.0%, Mo: 0.48%, Al: 1.43%, Ti: 3.44%, Nb: 3.13%, Fe: 0.02%, Mn: 0.044%, Si: 0.031%, C: 0.06%, B: 0.004%, Zr: 0.03%, with the balance being Ni and unavoidable impurities.

[0047] Comparative Example 4 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The pre-alloyed powder was prepared according to the following mass percentages: Co: 17.3%, Cr: 15.4%, W: 2.0%, Mo: 0.8%, Al: 1.6%, Ti: 2.8%, Nb: 0.5%, Fe: 0.03%, Mn: 0.03%, Si: 0.02%, C: 0.12%, B: 0.012%, Zr: 0.03%, with the balance being Ni and unavoidable impurities.

[0048] Comparative Example 5 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, with the only difference being: The additive manufacturing process (3D printing) parameters include: under the protection of high-purity argon gas, the single-layer thickness is set to 40 μm, the scanning spacing is 80 μm, the laser power is 150 W, the laser scanning rate is 1400 mm / s, and the laser spot diameter is 80 μm.

[0049] Comparative Example 6 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, except that the solution treatment conditions were: after holding at 1100℃ for 1 hour, it was air-cooled at a cooling rate of about 100℃ / min.

[0050] Comparative Example 7 The high-strength, high-toughness, oxygen-rich ablation-resistant nickel-based superalloy was prepared in a manner similar to that in Example 1, except that the aging treatment conditions were: after holding at 720°C for 15 h, it was air-cooled at a cooling rate of about 70°C / min.

[0051] Experimental Example Experiment Example 1 Mechanical Property Testing The nickel-based superalloys prepared in Examples 1-6 and Comparative Examples 1-7 were subjected to tensile tests at 650℃. The test standard adopted was GB / T 228.2-2015 "Metallic materials, tensile testing - Part 2: High temperature test method". The tensile strength, yield strength, elongation after fracture and reduction of area were obtained. The test results are shown in Table 1.

[0052] Table 1 Tensile properties at 650℃ for different additively manufactured specimens

[0053] As shown in Table 1, the nickel-based superalloys prepared in Examples 1-6 of this invention exhibit high tensile strength and yield strength. Furthermore, they also demonstrate higher elongation after fracture and reduction of area. Compared to Examples 1-6, Comparative Examples 1-2 show slightly lower tensile strength and yield strength, and exhibit significant brittleness, with elongation after fracture of only 2%-2.5%. Comparative Example 3 demonstrates the highest tensile strength and yield strength, but also high brittleness, with an elongation after fracture of only 5%. The nickel-based superalloys prepared in Comparative Examples 4-5 show significantly lower tensile strength, yield strength, elongation after fracture, and reduction of area. The nickel-based superalloy prepared in Comparative Example 6 shows significantly lower tensile strength and yield strength compared to Example 1. While the yield strength of the nickel-based superalloy prepared in Comparative Example 7 is improved compared to Example 1, its elongation after fracture is even lower.

[0054] Experimental Example 2 Metallographic Characterization Metallographic characterization was performed on the nickel-based superalloys prepared in Examples 1-4 and Comparative Examples 4-5, respectively. The test results are as follows: Figures 1-6 As shown, the alloy prepared in Comparative Example 1 was subjected to transmission electron microscopy (TEM) testing, and the test results are as follows. Figure 7 As shown, the alloy prepared in Example 1 was subjected to transmission electron microscopy (TEM) testing, and the test results are as follows. Figure 8 As shown.

[0055] Figures 1-4 The images shown are metallographic images of the nickel-based superalloys obtained in Examples 1-4 after polishing. Figure 5 and Figure 6The figures show the metallographic images of the nickel-based superalloys obtained in Comparative Examples 4 and 5 after polishing. As can be seen from Figures 1-4, the alloy samples obtained in Examples 1-4 of this invention are dense, with only a very small amount of unavoidable pores, the pore size of which is ≤10μm. In Comparative Example 4, the high C and B content leads to a large number of intergranular hot cracks, severely reducing the tensile properties of the material at 650℃. In Comparative Example 5, the use of an excessively low laser power of 150W and an excessively high scanning rate of 1400mm / s resulted in a large number of irregularly shaped, large-sized unfused defects in the alloy sample, severely reducing the tensile properties of the alloy material at 650℃.

[0056] Figure 7 The microstructure of the alloy sample prepared in Comparative Example 1 is shown below. Figure 7 As can be seen, a low Cr content in the alloy leads to only a small amount of TiC precipitates at the grain boundaries, resulting in insufficient grain boundary strengthening. The alloy sample prepared in Comparative Example 1 showed a slight decrease in tensile strength and yield strength at 650℃, and exhibited significant brittleness. In Comparative Example 2, the content of solid solution strengthening elements W and Mo was increased. Although the tensile strength and yield strength improved, brittleness still existed at 650℃, with an elongation after fracture of only 2.0%. In Comparative Example 3, the Nb content was increased, resulting in a significant improvement in the tensile strength and yield strength of the nickel-based superalloy, but brittleness still occurred at 650℃.

[0057] Figure 8 Transmission electron micrograph of the alloy prepared in Example 1, from Figure 8 As can be seen, in addition to forming the TiC strengthening phase at grain boundaries, the alloy composition of this invention also contains a large number of Cr-rich strengthening phases at grain boundaries, which ensures the strength of the alloy grain boundaries and thus improves the high-temperature strength and high-temperature elongation of the alloy.

[0058] The above results show that the proportion of each element in the nickel-based superalloy has a significant impact on the tensile strength, yield strength, elongation after fracture, and reduction of area of ​​the final superalloy. Only when the proportion of each element in the nickel-based superalloy is within the range defined by this invention can the final nickel-based superalloy have high tensile strength, yield strength, elongation after fracture, and reduction of area.

[0059] Experiment Example 3: Oxygen-enriched ablation performance test Oxygen-enriched combustion samples were prepared from the nickel-based superalloys obtained in Examples 1-6 and Comparative Examples 1-7, respectively. The sample dimensions were ф3.2×120mm, and the sample surface was bright and oil-free. Then, the oxygen-enriched ablation resistance performance was tested. The test conditions were room temperature, 9MPa, and pure oxygen. Al strips were used as ignition aids. The actual burning length of each sample was measured, and the test results are shown in Table 2.

[0060] Table 2. Test results of alloy combustion heat and oxygen-enriched ablation resistance of different additive manufacturing samples.

[0061] Combining Tables 1 and 2, it can be seen that the nickel-based superalloy samples prepared in Examples 1-4 of this invention, while taking into account additive manufacturing processability, high strength, and high toughness (Table 1), can control the calorific value of the nickel-based superalloy to below 6.0 kJ / g through precise control of the alloy composition. This nickel-based superalloy exhibits excellent resistance to oxygen-enriched ablation; that is, under test conditions of room temperature, 9 MPa, pure oxygen environment, and using Al strips as ignition aids, the actual burning length of the nickel-based superalloy is ≤20 mm. In Examples 5 and 6, although heat treatment can have some impact on high-temperature mechanical properties, it has little effect on the calorific value and resistance to oxygen-enriched ablation. The samples prepared in Comparative Examples 1, 2, and 5, although exhibiting low calorific values ​​and good resistance to oxygen-enriched ablation, show insufficient mechanical strength and severe brittleness at 650℃. The samples prepared in Comparative Examples 3 and 4, due to improper composition control, not only have mechanical properties that fail to meet application conditions, but also exhibit high calorific values ​​and poor resistance to oxygen-enriched ablation. Although the alloys prepared in Comparative Examples 6 and 7 had low calorific values ​​and good resistance to oxygen-enriched ablation, improper heat treatment control resulted in the alloys' high-temperature mechanical properties failing to meet the application requirements.

[0062] As can be seen from the above, this invention, through the design and control of the types and proportions of alloy components, improves the tensile strength, yield strength, and elongation at 650℃ while maintaining the additive manufacturing processability; simultaneously, it effectively controls the alloy's calorific value below 6.0 kJ / g, improving the alloy's resistance to oxygen-rich ablation. The high-temperature alloy and its additive manufacturing method provided by this invention can form complex parts while ensuring the tensile properties and resistance to oxygen-rich ablation of the alloy material, enabling it to meet the stringent requirements of key components such as liquid rocket engines.

[0063] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A high-strength high-ductility oxygen-rich ablation-resistant nickel-based superalloy, characterized in that, The high-strength and high-toughness anti-oxygen-rich ablation nickel-based superalloy material is prepared from raw materials including the following mass percentages: Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance being Ni and inevitable impurities. The high-strength and high-toughness anti-oxygen-rich ablation nickel-based superalloy material is prepared from raw materials including the following mass percentages:

2. The high-strength and high-ductility oxygen-rich ablation-resistant nickel-based superalloy according to claim 1, characterized in that, Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance being Ni and inevitable impurities. The high-strength and high-toughness anti-oxygen-rich ablation nickel-based superalloy material is prepared from raw materials including the following mass percentages: Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance being Ni and inevitable impurities.

3. The high-strength and high-ductility oxygen-rich ablation-resistant nickel-based superalloy according to claim 2, characterized in that, The high-strength and high-toughness anti-oxygen-rich ablation nickel-based superalloy material is prepared from raw materials including the following mass percentages: Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance being Ni and inevitable impurities.

4. The high-strength and high-ductility oxygen-rich ablation-resistant nickel-based superalloy according to claim 2, characterized in that, The high-strength and high-toughness anti-oxygen-rich ablation nickel-based superalloy material is prepared from raw materials including the following mass percentages: Co: 12% to 18%, Cr: 14% to 18%, W: 0% to 4%, Mo: 0% to 1%, Al: 0.5% to 2.0%, Ti: 1.5% to 3.5%, Nb: 0% to 1.0%, Fe: 0% to 0.5%, Mn: 0% to 0.5%, Si: 0% to 0.5%, C: 0.01% to 0.08%, B: 0.001% to 0.01%, Zr: 0.01% to 0.05%, and the balance being Ni and inevitable impurities.

5. The high-strength and high-ductility oxygen-rich ablation-resistant nickel-based superalloy according to claim 2, characterized in that, The additive manufacturing method comprises the following steps: Step 1, preparing an additive sample by additive manufacturing process through weighing each metal and non-metal raw material; 6. The additive manufacturing method of high-strength and high-ductility, oxygen-rich ablation-resistant nickel-based superalloy according to any one of claims 1 to 5, characterized in that, Step 2, performing solid solution treatment on the additive sample, then performing aging treatment after air cooling, and then air cooling to obtain a nickel-based superalloy. In step 1, ​ 7. The additive manufacturing method of claim 6, wherein, ​ The conditions of the additive manufacturing process are: under vacuum or protective atmosphere, the single layer thickness is 20-40 microns, the scanning interval is 60-100 microns, the laser power is 200-300 W, the laser scanning rate is 800-1300 mm / s, and the laser spot diameter is 60-100 microns.

8. The additive manufacturing method of claim 6, wherein, In step 2, The conditions of the solid solution treatment are: heat preservation at a temperature of 940-1000 DEG C for 1-5 hours.

9. The additive manufacturing method of claim 6, wherein, In step 2, The conditions of the aging treatment are: heat preservation at a temperature of 690-750 DEG C for 6-12 hours.